Current practices of plastic waste management, environmental impacts, and potential alternatives for reducing pollution and improving management - Md Atik Fayshal (Heliyon)
Plastic products are indispensable across various applications, yet their disposal poses significant environmental hazards, such as groundwater contamination, soil degradation, and marine ecosystem threats, impacting both human health and ecological balance. Key issues include rapid development and population growth, inadequate technical skills for hazardous waste management, insufficient infrastructure for recycling, and a general lack of awareness regarding regulations. This study offers a comprehensive analysis of plastic waste generation, its sources, current management practices, and its environmental impacts, along with mitigation measures. Globally, predictions indicate that plastic production could exceed 650 million tons by 2050, representing a staggering more than 22000 % increase compared to 1950, highlighting the pressing need for action. Moreover, due to their chemical structures and prolonged degradation periods, plastic waste (PW) can lead to cancer, nervous system damage, rapid genetic changes, and metabolic disorders in humans. In that scenario, waste-to-energy and product conversion strategies through thermochemical conversion techniques can be a double-edged solution by minimizing waste along with providing value-added products. Also, using alternatives to plastic, including bio-plastics, stainless steel, glass, platinum silicon, wood, bamboo, cardboard, paper, cotton, pottery, ceramics, and more, can be a viable pathway for proper PW management. The successful incorporation of the proposed alternative products holds promise for improving the overall management of plastic waste. Additionally, this study highlights sustainable waste management practices and outlines the primary challenges in implementing effective strategies to reduce the negative impact of plastic waste.